Gender differences in self-care for common colds by primary care patients: a European multicenter survey on the prevalence and patterns of practices (the COCO study). Issue 7 (3rd October 2021) - Hoffman, Robert D.; Thielmann, Anika; Buczkowski, Krzysztof; Edirne, Tamer; Hoffmann, Kathryn; Koskela, Tuomas; Lingner, Heidrun; Mevsim, Vildan; Tekiner, Selda; Zielinski, Andrzej; Hoffman Cicurel, Naomi; Petrazzuoli, Ferdinando; et al.
ABSTRACT: Although generally harmless, the common cold disturbs the lives of billions yearly. It is frequently treated by self-care, yet little is known about the effect gender may have on self-care. Our study set out to discover whether self-care for common colds differs by gender. We also wanted to test the 'Man cold' belief: that men 'break down' when they have a cold and suffer more than women when they are sick. We distributed questionnaires asking for a selection of self-care practices in eight categories to 3, 240 consecutive patients in 14 Eurasian countries at 27 primary care sites. Of 2, 654 patients included, 99% reported engaging in self-care for common colds. Discomfort was reported more frequently by women (74.7% vs. 66.5%, p < 0.001). There were gender differences in several self-care categories. The mean use of self-care items was higher in women than in men (12.0 vs. 10.3, p < 0.001). Women reported a greater variety of self-care items than men. However, more men reported using alcohol (17.8% vs. 8.4%, p < 0.001). This cross-national study documented gender differences in self-care for common colds.